Necessity of Establishing a UN Specialized Agency for Protection of Gender Equality - Shokrani, Maziyar; Many, Nirmala (Indonesian Journal of International Law, 2022)
A number of recent global issues such as COVID, rise of the Taliban in Afghanistan, inter-state and intra-state conflicts, and gender inequality in Iran show the unprecedented violence against women and other disadvantaged segments of the societies around the globe despite the restless efforts of existing organizations such as the UN Women to protect women’s right, and in broader sense promote gender equality. The lack of efficiency is partly due to its institutional capacities e.g. lacking independence, founding treaty, law-making/treaty making powers and, developed institutional structures and enforcement powers. This article investigates the shortcomings of the UN Women in fulfilling its targets and some of the major reasons behind it. The authors suggest the UN Women to transform to a UN Specialized Agency with wide law-making and treaty-making powers as well as the powers of on-site inspections and reporting to the UN- more specifically to the Security Council as the gender equality is directly connected to the global peace and security.